ASME 2012 Internal Combustion Engine Division Fall Technical Conference 2012
DOI: 10.1115/icef2012-92162
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Reduction From a Pilot-Ignited, Direct Injection of Natural Gas Engine

Abstract: This paper reports an evaluation of various combustion strategies aiming to reduce engine-out particulate matter (PM) emissions from a natural-gas fuelled heavy-duty engine. The work is based on a Westport HPDI fuelling system, which provides direct injection of both natural gas and liquid diesel into the combustion chamber of an otherwise unmodified diesel engine. The diesel acts as a pilot to ignite the natural gas, which normally burns in a non-premixed fashion, leading to significant PM formation. The conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The natural gas is then ignited by the diesel pilot flame. The natural gas combustion is predominately unmixed, which helps avoid knock and allows for a high-compression ratio and thermal efficiency, like those associated with diesel engines (McTaggart-Cowan et al 2012). In this engine, soot particles are mainly formed by incomplete combustion of natural gas (Jones 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural gas is then ignited by the diesel pilot flame. The natural gas combustion is predominately unmixed, which helps avoid knock and allows for a high-compression ratio and thermal efficiency, like those associated with diesel engines (McTaggart-Cowan et al 2012). In this engine, soot particles are mainly formed by incomplete combustion of natural gas (Jones 2004).…”
Section: Introductionmentioning
confidence: 99%
“…They determined that PM mass emissions were affected primarily by EGR and EQR, and PM number emissions were also affected by EGR and EQR, and less strongly by GRP and diesel pilot quantity. McTaggart-Cowan et al (2012) worked to reduce the PM mass emissions for the same engine mode used by Patychuk and Rogak (2012). They found that PM could be reduced by adjusting the relative phasing of the diesel and natural gas injections to allow for more premixing of the natural gas with air.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits include improvements in thermal efficiency through increasing the flame speed of NG resulting from the combustion of locally stoichiometric NG-air mixture [13]. However, the main drawbacks of this method include the increased complexity of the injection system due to the high injection pressure and the increase in soot emissions due to the presence of rich mixture zones [14,15]. Engine simulations are valuable tools for evaluating the performance and emission parameters.…”
Section: Introductionmentioning
confidence: 99%